2022
DOI: 10.1200/jco.21.02004
|View full text |Cite
|
Sign up to set email alerts
|

Linking Structural Racism and Discrimination and Breast Cancer Outcomes: A Social Genomics Approach

Abstract: Society to Cells to OutcomesWe live in a society where individuals and communities are marginalized because of their race or ethnicity. This structural inequity extracts enormous health and societal costs, decreasing access to cancer care and increasing health disparities, especially among the most vulnerable. In an effort to identify causes of disparities, we have incorporated individual sociodemographic characteristics (eg, income and education) and other social determinants of health (eg, access to care, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 84 publications
(119 reference statements)
2
14
0
Order By: Relevance
“…Potential biologic mechanisms underpinning relationships involving breast cancer outcomes, self-identified race and ethnicity, and interpersonal and structural racism could involve chronic psychosocial stress and genomic markers of inflammation (eg, DNA methylation or gene expression of interleukin receptors, C-reactive protein). 43 , 44 , 45 Empirical studies designed explicitly to test whether stress and genomic inflammatory markers mediate associations between racism and breast cancer are lacking. However, one study has reported differential breast tumor methylation of numerous genes by neighborhood socioeconomic factors, with at least 1 such gene also correlating with mortality following a breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential biologic mechanisms underpinning relationships involving breast cancer outcomes, self-identified race and ethnicity, and interpersonal and structural racism could involve chronic psychosocial stress and genomic markers of inflammation (eg, DNA methylation or gene expression of interleukin receptors, C-reactive protein). 43 , 44 , 45 Empirical studies designed explicitly to test whether stress and genomic inflammatory markers mediate associations between racism and breast cancer are lacking. However, one study has reported differential breast tumor methylation of numerous genes by neighborhood socioeconomic factors, with at least 1 such gene also correlating with mortality following a breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 Stress and inflammatory pathways have been proposed as possible biologic mediators between racism and health outcomes, including breast cancer outcomes, and potential contributors to racial and ethnic disparities. 1 , 43 , 44 , 45 Accordingly, this study investigates associations between 1930s-era HOLC redlining, racial and ethnic identity, and breast cancer stage, grade, TNBC, and mortality among women diagnosed between 2008 and 2017 while a resident of a metropolitan area of New Jersey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biologic and social environmental factors interact to affect cancer outcomes across all ages of cancer survivors. A social genomics approach to outcomes research in cancer suggests a biologic component of psychological and social influences on disease by identifying neural and molecular pathways through which psychological and social factors mechanistically influence disease development and progression (see general reviews 10,14 and cancer-specific reviews 13,[15][16][17]. Figure 1 shows a conceptual framework of social genomics in cancer survivorship by which biologic mechanisms and gene expression attenuate the effects of specific psychological and social risk and resilience factors (eg, poverty, exposures to trauma, social isolation, behavioral self-efficacy, and meaning attribution) on health outcomes and QOL for cancer survivors.…”
Section: Social Genomic Approaches To Research In Cancer Survivorshipmentioning
confidence: 99%
“…Numerous studies have reported significant disparities in cancer care arising from sociodemographic characteristics and other social determinants of health [ 11 16 ]. DCIS has been also reported disparities in outcomes [ 13 , 14 ]. However, DCIS treatment patterns according to patient characteristics and treatment locations have not been clearly elucidated or assessed.…”
Section: Introductionmentioning
confidence: 99%